2018
DOI: 10.1103/physrevlett.121.130406
|View full text |Cite
|
Sign up to set email alerts
|

Contact and Momentum Distribution of the Unitary Fermi Gas

Abstract: A key quantity in strongly-interacting resonant Fermi gases is the contact C, which characterizes numerous properties such as the momentum distribution at large momenta or the pair correlation function at short distances. The temperature dependence of C was measured at unitarity, where existing theoretical predictions differ substantially even at the qualitative level. We report accurate data for the contact and the momentum distribution of the unitary gas in the normal phase, obtained by Bold Diagrammatic Mon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 64 publications
(107 reference statements)
6
67
0
Order By: Relevance
“…4. Very recently, these results were confirmed using a much more advanced resumma-tion method, which was found to be necessary for controllability, due to the fact that the series has zero radius of convergence 12 . Contact and momentum distribution were also computed using the new resummation method 13 .…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…4. Very recently, these results were confirmed using a much more advanced resumma-tion method, which was found to be necessary for controllability, due to the fact that the series has zero radius of convergence 12 . Contact and momentum distribution were also computed using the new resummation method 13 .…”
Section: Introductionmentioning
confidence: 74%
“…A crucial separate aspect of the approach is the construction of an appropriate divergent-series resummation method; this was reported in Ref. 12 and will be detailed elsewhere 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Note that, these results are equivalent those given by Eqs. (18)(19)(20)(21) of Ref. [92] except that the sign convention for the scattering length is different (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Starting from the expansion (21) and making a Taylor expansion of each terms around k = k F (or p = 1), one obtains a systematic approach to compute quasi-particle properties in powers of (a s k F ). For instance using the Taylor expansion:…”
Section: Self-energy For Fermi Systems At Low Densitymentioning
confidence: 99%
“…In Ref. [54], the equation of state of the homogeneous unitary Fermi gas has been accurately calculated by the diagrammatic Monte Carlo calculation. The authors have found that the equation of state as a function of e βµ shows a non-monotonic behaviour at e βµ ∼ 1, in a similar manner as that explained above to a har-monically trapped system.…”
Section: Fourth Order Virial Expansion Coefficient In the Unitary Fermentioning
confidence: 99%